Trailblazing medicine sustaining explorers during interplanetary missions - Seedhouse, Erik.; SpringerLink (Online service). (New York Springer, 2011)
To prepare for the day when astronauts leave low-Earth orbit for long-duration exploration missions, space medicine experts must develop a thorough understanding of the effects of microgravity on the human body, as well as ways of mitigating them. To gain a complete understanding of the effects of space on the human body and to create tools and technologies required for successful exploration, space medicince will become an increasingly collaborative discipline incorporating the skills of physicians, biomedical scientists, engineers, and mission planners. Trailblazing Medicine examines the future of space medicine in relation to human space exploration; describes what is necessary to keep a crew alive in space, including the use of surgical robots, surface-based telemedicine, and remote emergency care; discusses bioethical problems such as euthanasia, sex, and precautionary surgery; investigates the medical challenges faced by interplanetary astronauts; details the process of human hibernation.
Electronic reproduction.
Keywords: Space medicine; Astronauts -- Medical examinations; Electronic books